A Decision Support Model for Assessing Co‐Creation: The Bee Path Project - Tina Jukić; Sanja Vrbek (Urban Planning)
This article presents a decision support model (DSM) for assessing the quality of co‐creation processes and critically reflects on its applicability in the context of climate change mitigation in urban settings. While cities have become pivotal in addressing climate change, often through co‐creation, tools for evaluating urban climate‐related co‐creation initiatives remain scarce. Rather than advocating for a tool specifically designed for this context, the article seeks to offer a universal DSM developed through a systematic literature review and empirical case studies within the framework of the COGOV Horizon project. The DSM incorporates 19 attributes across three phases of co‐creation: stakeholder identification and mobilisation, the act of co‐creation, and its effects. The model is tested on the Bee Path initiative of the City of Ljubljana, a successful co‐creation project aimed at fostering a bee‐friendly urban environment and promoting self‐sufficiency. The results confirm the DSM’s applicability in assessing the success of co‐creation in the context of climate change policies at the city level of governance. Moreover, this tool offers a foundation model for further integration with emerging technologies to enhance decision‐making and guidance for public organisations. As such, the DSM serves as a practical tool enabling public organisations to critically reflect on their roles in co‐creation initiatives, identify areas for improvement, and enhance their capacity as co‐creators in future urban climate policies and beyond.